2013
DOI: 10.1016/j.cmet.2013.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Tam41 Is a CDP-Diacylglycerol Synthase Required for Cardiolipin Biosynthesis in Mitochondria

Abstract: SUMMARY CDP-diacylglycerol (CDP-DAG) is central of the phospholipid biosynthesis pathways in cells. A prevailing view is that only one CDP-DAG synthase named Cds1 is present in both the endoplasmic reticulum (ER) and mitochondrial inner membrane (IM), and mediates generation of CDP-DAG from phosphatidic acid (PA) and CTP. However, we demonstrate here by using yeast Saccharomyces cerevisiae as a model organism that Cds1 resides in the ER but not in mitochondria, and that Tam41, a highly conserved mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(143 citation statements)
references
References 51 publications
4
138
0
1
Order By: Relevance
“…7C) (albeit with reduced levels of AAC). Tam41 is a CDP-diacylglycerol synthase required for CL biosynthesis in mitochondria, and thus, like the ⌬crd1, ⌬tam41 mitochondria are deficient in CL (31). Interestingly, despite being reduced in levels, a population of Taz1, an enzyme involved in remodeling of CL, was recovered in association with the affinity-purified rcf1 His R67A protein (Fig.…”
Section: R67amentioning
confidence: 99%
“…7C) (albeit with reduced levels of AAC). Tam41 is a CDP-diacylglycerol synthase required for CL biosynthesis in mitochondria, and thus, like the ⌬crd1, ⌬tam41 mitochondria are deficient in CL (31). Interestingly, despite being reduced in levels, a population of Taz1, an enzyme involved in remodeling of CL, was recovered in association with the affinity-purified rcf1 His R67A protein (Fig.…”
Section: R67amentioning
confidence: 99%
“…Mitochondria are also equipped with a family of carriers that facilitate the transport of small soluble molecules like amino acids, nucleotides, and vitamins across the mitochondrial inner membrane, necessary for the interdependent metabolism at both sides of the mitochondrial double membrane (76,77). Mitochondria also play an important role in lipid metabolism (28,29,31,78): it is the site of synthesis of the mitochondrial-specific PLs, CL, and PG, generated from PA, which is imported from the ER (Fig. 1).…”
Section: Making Mitochondrial Membranes: the Contribution Of Er-mitocmentioning
confidence: 99%
“…The first methylation is carried out by Cho2 and the second and third by Opi3. PA is also transported to the mitochondria where it is converted to CDP-DAG by the activity of the mitochondrial CDP-DAG synthase, Tam41 (28), for subsequent synthesis of the mitochondrial-specific lipids, phosphatidylglycerol (PG) by Pgs1/Gep4 and cardiolipin (CL) by Crd1 ( Fig. 1) (29)(30)(31).…”
mentioning
confidence: 99%
“…Liposomes based reconstitution of the purified translocase revealed that the minimal unit for preprotein integration into the inner membrane is the four-subunit TIM23 complex, a cardiolipin-rich membrane, and a membrane potential. Cardiolipin is the characteristic dimeric phospholipid of mitochondrial inner membrane (Acehan et al, 2011; Bihlmaier et al., 2008; Corcelli et al, 2010;Tamura et al, 2013). Preproteins following this insertion pathway into the inner membrane contain a hydrophobic sorting signal behind the matrix-targeting signal.…”
Section: Devanjan Sinhamentioning
confidence: 99%